An Experimental Approach towards PV-Based Solar System Sizing for an Engineering Laboratory - Lawal, Muyideen O.; Bada, Olalekan M.; Ajewole, Titus O.; Ashaolu, Samuel O. (Tanzania Journal of Engineering and Technology, 2022)
This study aims at providing an experimental sizing procedure for a rooftop PV-based solar power system for an engineering laboratory. This was achieved by monitoring the peak power and energy delivered by an installed 20W solar panel into an 18 Ah battery. Knowledge of the average daily peak power and energy was used to determine the percentage rated capacity available for use and the sun hour. A load consumption comparison was also carried out with and without the connection of a load to inverter. In addition to this, the monitoring of the no-load consumption of the inverter was carried out. This was carried-out to ascertain the contribution of the inverter to the system. With the knowledge of the average daily energy deliverable, sun hour and the no-load power of the inverter, a sample sizing for basic electronic laboratory loads was done. The findings of the study reveals that the average available power is 89.35% of the solar panel rated capacity while the average sun hour is 4.38 h. It has also been shown that an approximate difference of 20 W exists between the power consumption of the load with and without its connection to the inverter. This value (i.e., 20W) has been recorded as the approximate no-load power for the inverter. The sample sizing done has shown that, the solar panel energy requirement of the system with inverter may be considerably higher than that without inverter. Keywords: solar energy, average sun hour, no-load power, deliverable power, sizing.